MENINGKATKAN MOTORIK HALUS MELALUI KEGIATAN KOLASE MENGGUNAKAN CANGKANG TELUR PADA ANAK KELOMPOK B TK FLAMBOYAN SARITA DESA PUNTI KECAMATAN SOROMANDI BIMA (NTB) - Kusmiati; Nur Alim Amri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Improving Fine Motorics Through Collage Activities Using Eggshells in Group B Children of the Flamboyan Sarita Kindergarten, Punti Village, Soromandi Bima District (NTB). Thesis. The main problem in this study is how to improve fine motor skills through collage activities using eggshells for children in Group B Kindergarten Flamboyan Sarita, Punti Village, Soromandi District, Bima (NTB). This study aims to improve fine motor skills through collage activities using eggshells in group B children at the Flamboyan Sarita Kindergarten, Punti Village, Soromandi Bima District (NTB). This type of research is class action research (Classroom Action Research) which consists of two cycles where each cycle is held in two meetings. Research procedures include planning, implementation of action, observation and reflection. The subject of this study was Group B Kindergarten Flamboyan Sarita, Punti Village, Soromandi Bima District (NTB). The results showed that there was an increase in fine motor skills through collage activities using eggshells in group B children at the Flamboyan Sarita Kindergarten, Punti Village, Soromandi Bima District (NTB). Improving fine motor skills in collage activities using egg shells which includes 3 indicators, drawing patterns, sticking egg shells on patterns, cutting the collage results according to patterns. Based on the results of the research above, it can be interpreted that the ability to improve fine motor skills through collage activities using eggshells in group B children at the Flamboyan Sarita Kindergarten, Punti Village, Soromandi Bima District (NTB). Increased.